2010
DOI: 10.1007/s12576-010-0103-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and local visfatin/Nampt/PBEF levels in spontaneously hypertensive rats, stroke-prone spontaneously hypertensive rats and Wistar-Kyoto rats

Abstract: Visfatin (also known as nicotinamide phosphoribosyltransferase and pre-B cell colony-enhancing factor) is a multifunctional protein. Visfatin has been reported to be involved in several biological processes in the cardiovascular system, . However, the role of visfatin in hypertension is still unclear. In this study, we examined the circulating and local adipose visfatin levels in spontaneously hypertensive rats (SHR), stroke-prone spontaneously hypertensive rats (SHR-SP), and in their normotensive control Wist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
(36 reference statements)
2
12
1
Order By: Relevance
“…A recent animal study showed that visfatin is a myokine, secreted from skeletal muscle cells in a hypertensive rat model (22). In that study serum visfatin levels were not statistically different in hypertensive and normotensive rats.…”
Section: Discussionmentioning
confidence: 71%
“…A recent animal study showed that visfatin is a myokine, secreted from skeletal muscle cells in a hypertensive rat model (22). In that study serum visfatin levels were not statistically different in hypertensive and normotensive rats.…”
Section: Discussionmentioning
confidence: 71%
“…In a recent study, we demonstrated that visfatin, a PVAT‐derived growth factor for vascular smooth muscle cells (VSMC), is highly expressed in PVAT compared with subcutaneous and visceral fat 75 . We also provided evidence that visfatin is involved in cardio‐ and cerebrovascular disease 76–79 . Other studies have shown that visfatin induces inducible nitric oxide synthase and elicits sustained activation of extracellular signal‐regulated kinase (ERK) 1/2 signalling with the induction of NF‐κB in VSMC 80 .…”
Section: Adipokines Inflammation and Cardiovascular Diseasementioning
confidence: 73%
“…This assay has a limit of detection of ≤0.10 µg/L, with interassay and intraassay coefficients of variation of 2.3% and 5.1%, respectively. The homeostasis model assessment of insulin resistance (HOMA-IR) index was calculated using the following formula [31], [32]: HOMA-IR = fasting blood insulin (mIU/L)×fasting blood glucose (mmol/L)/22.5. The quantitative insulin sensitivity check index (QUICKI) was calculated according to the original formula [33] as the inverse log sum of fasting insulin in mIU/L and fasting glucose in mg/dl.…”
Section: Methodsmentioning
confidence: 99%